Strategy Of Tahfiz Ocean Quran House In Eradication Letters Of The Quran At Sei Putih Timur Village - Mardia Ulfa Hasibuan (-, 2022)
This study aims to: Find out the strategies used by Rumah Quran Samudera Tahfiz in the Eradication of Quran Illiteracy in Sei Putih Timur Village. To find out the obstacles and solutions applied by Ustadzah during the learning process at the Samudera Tahfiz Quran House. This type of research is a qualitative research. This research was conducted by collecting data, namely: interviews, observations, documentation. The results obtained were the method of learning the Qur'an and the steps in dealing with eradicating illiteracy in the Qur'an in the village of Sei Putih Timur.